Temperature distribution and flow field characteristics of multiple fire whirls in a vertical shaft - Rongshui Qin; Lingfeng He; Xuesong Dai; Zijian Yan; Zelong Zhang; Chao Ding; Yan Jiao (Case Studies in Thermal Engineering)
This paper investigates the temperature distribution and flow field characteristics of multiple fire whirls in a vertical shaft. The pool number n, diameter D, and dimensionless flame spacing S/D (S: flame spacing) were varied. The results suggest that the merged flame zone in multiple fire whirls includes three different zones similar to pool fires, namely continuous flame, intermittent flame and plume. A simplified flame shape model is established for two pool numbers, using the flame merging point as a boundary. A correlation between the normalized height of the merged flame zone and the centerline excess temperature distribution is developed by introducing a virtual origin to represent the effect of fire geometry. The results also indicate that the increase in circulation enlarges the contact area between the flame and fuel, inducing more air into the merged flame zone and enhancing the burning rate, and an optimum flame spacing exists to maximize it. Furthermore, based on the flame trailing effect, a relationship is established for the tangent values of the outer burners’ flame tilt angles in multiple fire whirls, varying with induced wind speed under different controlling parameters. It is revealed that flame tilt angle shows a non-linear increase with wind intensity and the theoretical predictions agree well with the experimental results. Finally, numerical simulations characterize the flow distribution around multiple fire whirls. It is found that with increasing S/D, whirls are mainly concentrated in the central region of the merged flames, with the surrounding areas being relatively weaker. Simultaneously, a critical S/D exists where the maximum tangential velocity peaks, influenced by competing interactions from the flames. Besides, the maximum tangential velocity shows a monotonic increase with the increase of S/D in some experimental conditions, influenced by the number and size of pools.